Estimation of vector parameter by the method of maximization of power polynomial mean value/ - Игнатов, В. А.; Лега, Ю. Г.; Первунинский, С. М. (Proceedings of National Aviation University (archive), 2000)
Considered is the algorithm of vector parameter estimation by means of maximization of functional power polynomial mean value. The worked out algorithm provides for more simple program and technical realization of estimation devices